Modelling volatility of the exchange rate of the Naira to major currencies - Reuben O. David; Hussaini G. Dikko; Shehu U. Gulumbe (CBN Journal of Applied Statistics, 2016)
The exchange rate between the Naira and other currencies has continued to witness variability with depreciation. This variability makes it difficult to predict returns. Against this background, this paper examines the naira exchange rate vis-a-vis four other currencies. The impact of exogenous variables in modelling volatility is considered using both the GARCH (1,1) and its asymmetric variants. Three of the four returns series showed heteroscedasticity. The results of the fitted models indicate that the majority of the parameters are significant and that volatility is quite persistent. Furthermore, the results of the asymmetric model indicate different impacts for both negative and positive shocks and shows superior forecasting performance to the symmetric GARCH.
Keywords: C52; C87; E44; E58; F31; 330; Exchange Rate; Volatility; Leverage Effects; Exogenous Variables; Persistence; Heteroscedasticity